2023
DOI: 10.3847/2041-8213/acf4ff
|View full text |Cite
|
Sign up to set email alerts
|

Change of Spectral Properties of Magnetic Field Fluctuations across Different Types of Interplanetary Shocks

Byeongseon Park,
Alexander Pitňa,
Jana Šafránková
et al.

Abstract: The interaction between interplanetary (IP) shocks and the solar wind has been studied in the past for the understanding of energy dissipation mechanisms within collisionless plasmas. Compared to the study of fast shocks, other types of IP shocks, including slow mode shocks (i.e., fast forward, fast reverse, slow forward, and slow reverse shocks) remained largely unnoticed. We analyze magnetic field fluctuations observed by the Wind spacecraft from 1995 to 2021 upstream and downstream of the IP shocks using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…However, because the downstream flow speed is much larger than the upstream, and the shock changes the plasma parameters abruptly, the level of fluctuations may be overestimated. While the increase in the level of the frequency spectrum has been documented in previous literature (Zhao et al 2021;Park et al 2023), it remains to be understood whether IP shocks inject new turbulence or they simply modify the background plasma properties. However, preliminary analysis shows that the spectral break happens around the ion skin depth d i , compatible with statistical work carried out by Park et al (2023).…”
Section: Event Overviewmentioning
confidence: 89%
See 1 more Smart Citation
“…However, because the downstream flow speed is much larger than the upstream, and the shock changes the plasma parameters abruptly, the level of fluctuations may be overestimated. While the increase in the level of the frequency spectrum has been documented in previous literature (Zhao et al 2021;Park et al 2023), it remains to be understood whether IP shocks inject new turbulence or they simply modify the background plasma properties. However, preliminary analysis shows that the spectral break happens around the ion skin depth d i , compatible with statistical work carried out by Park et al (2023).…”
Section: Event Overviewmentioning
confidence: 89%
“…While the increase in the level of the frequency spectrum has been documented in previous literature (Zhao et al 2021;Park et al 2023), it remains to be understood whether IP shocks inject new turbulence or they simply modify the background plasma properties. However, preliminary analysis shows that the spectral break happens around the ion skin depth d i , compatible with statistical work carried out by Park et al (2023). Further studies on the matter, relevant also for understanding the behavior of turbulence at very low heliocentric distances (Zank et al 2020), are further complicated by the geometrical constraints imposed by the singlespacecraft nature of the observations.…”
Section: Event Overviewmentioning
confidence: 89%
“…Clearly, κ ⊥ has a weaker A/Q dependence than κ ∥ . A recent statistical study by Park et al (2023) found that β ranges from −1.4 to −2.0, both downstream and upstream of the fast forward and fast reverse interplanetary shock, with a mean value around −1.7. In this work, we assume β to be −5/3 when considering the transport of energetic ions in the solar wind, away from the reverse shock.…”
Section: Modelmentioning
confidence: 99%
“…A case study of the large 2003 October 29 event (Li et al 2005a) showed an enhancement of more than a factor of 10. Recent work by Park et al (2023) suggested that the turbulence level across fast shocks can increase, on average, by 3-5 times. From the rarefaction region, the spectral index β does not differ much from the Kolmogorov value.…”
Section: Modelmentioning
confidence: 99%
“…Recently, a number of studies focused on the interaction of turbulent fluctuations and MHD shocks from both theoretical and observational perspectives (Adhikari et al 2016;Pitňa et al 2017Pitňa et al , 2021Borovsky 2020;Zank et al 2021;Trotta et al 2022a;Park et al 2023). In particular, Zank et al (2021, hereafter Zank21) introduced a theoretical framework for the transmission of magnetic field fluctuations across highly perpendicular shocks with high upstream plasma beta values (β > 1).…”
Section: Introductionmentioning
confidence: 99%